The Hermeneutics of Silk: China and the Fabric of Christendom according to Martino Martini and the Early Modern Jesuit "Accommodationists". (18th April 2019) - Yeh, Alice
Abstract: As Jesuit missionaries in seventeenth-century China struggled to translate Christian theology into Chinese terms and categories, they embarked on a project of purifying the "political" from the "superstitious." Their project was structured by the unmentionable: the proscribed luxury of silk robes that facilitated the encounters between the missionaries and the native elite they most sought to convert. This article examines the manifold functions of silk and the problem of "accommodation" by turning to the Brevis relatio de numero et qualitate Christianorum apud Sinas ("Brief report on the number and quality of Christians in China"), a booklet authored by the Jesuit missionary Martino Martini (1614–1661). Written for European circulation, the Brevis relatio touted the triumphs of the mission by incorporating the conceptual imaginary of "China" into the cosmo-political confines of the Euro-Christian world. This article shows how the basic Christian metaphor of horticultural fruitfulness was used to interpret silk and sericulture as material evidence that the Chinese mission field prefigured and promised, both spiritually and commercially, a profitable harvest.